Sistem Pendidikan Islam Berwawasan Multikultural Di Negara Negara Asean (Malaysia, Filipina, Singapura Dan Brunei Darussalam) - Rossi Delta Fitrianah (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2018)
In the world of education, multicultural discourse is a relatively new phenomenon. Multicultural education began to be known after World War II. In other words multicultural education is a new symptom in the association of humanity who longs for equal rights, including he right to get the same education, for all people (education for all). Southeast Asia has its own history that is rich in diversity and participation. Some Western researchers describe the West as a carrier of pluralist world tolerance, Western Imperialism will have a direct influence on the four Southeast Asian societies, namely the deterioration and rigidity of ethnoreligious differences such as those in West Colonial.